Effects of dams on river flow regime based on IHA/RVA - Q. Zuo; S. Liang; S. Liang (Proceedings of the International Association of Hydrological Sciences, 2015)
The river hydrologic regime is a driving force of the river ecosystem. Operation of dams and sluices has significant impacts on rivers’ hydrological situation. Taking the example of the Shaying River, the Jieshou hydrologic section was selected to study the influence of the sluice and all its upstream dams on the hydrologic regime. Using 55 years of measured daily flows at Jieshou hydrologic station, the hydrological date were divided into two series as pre- and post-impact periods. Based on the IHA, the range of variability in 33 flow parameters was calculated, and the hydrologic alteration associated with dams and sluices operation was quantified. Using the RVA method, hydrologic alteration at the stream gauge site was assessed to demonstrate the influence of dams on the hydrological condition. The results showed that dams have a strong influence on the regime; the river eco-hydrological targets calculated in this study can afford some support for water resources and ecosystem management of Shaying River.